2015 IEEE Conference on Computer Vision and Pattern Recognition Workshops (CVPRW) 2015
DOI: 10.1109/cvprw.2015.7301270
|View full text |Cite
|
Sign up to set email alerts
|

From generic to specific deep representations for visual recognition

Abstract: Evidence is mounting that ConvNets are the best representation learning method for recognition. In the common scenario, a ConvNet is trained on a large labeled dataset and the feed-forward units activation, at a certain layer of the network, is used as a generic representation of an input image. Recent studies have shown this form of representation to be astoundingly effective for a wide range of recognition tasks. This paper thoroughly investigates the transferability of such representations w.r.t. several fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
304
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(321 citation statements)
references
References 33 publications
(23 reference statements)
6
304
0
Order By: Relevance
“…The model saved at 200,000 iterations was always the source model. This is in line with the research done by Azizpour et al [21], which found that early stopping was less beneficial than overfitting, although the benefit of overfitting diminishes beyond 200,000 iterations.…”
Section: Experimental Framework and Datasetsupporting
confidence: 79%
See 1 more Smart Citation
“…The model saved at 200,000 iterations was always the source model. This is in line with the research done by Azizpour et al [21], which found that early stopping was less beneficial than overfitting, although the benefit of overfitting diminishes beyond 200,000 iterations.…”
Section: Experimental Framework and Datasetsupporting
confidence: 79%
“…The work of both Razavian et al [20] and Azizpour et al [21] also focuses on applying CNNs to other problems. In general, they find that CNNs coupled with SVMs provide competitive results to existing state-of-the-art solutions for many datasets.…”
Section: Related Work In Transfer Learning For Cnnsmentioning
confidence: 99%
“…For instance, reusing the first layers of a network have been shown to be an extremely good base representation of the visual information [17,29]. More specifically, applications of pre-trained CNN to the problem of visual instance retrieval have been studied in [6,8,30] on the classic Oxford5k, Paris5k and Holidays benchmarks. Building on these analysis, we use the VGG16 CNN architecture [34] as our base network (see Fig.…”
Section: Cnn Methodsmentioning
confidence: 99%
“…Using CNNs trained for object recognition has a long history in computer vision and machine learning. While they have been known to yield good results on supervised image classification tasks such as MNIST for a long time [17], recently they were not only shown to outperform classical methods in large scale image classification tasks [13], object detection [9] and semantic segmentation [8] but also to produce features that transfer between tasks [7], [2]. This recent success story has been made possible through optimized implementations for high-performance computing systems, as well as the availability of large amounts of labeled image data through, e.g., the ImageNet dataset [19].…”
Section: Related Workmentioning
confidence: 99%